Impact of a strength intervention program on change of hamstrings: quadriceps ratio and on change of 1 repetition maximum - Hammerová, T.; Králová, T.; Cacek, J.; Kalina, T.; Hlavonová, Z.; Ondrácek, J. (Studia Sportiva, 2019)
The relationship between the muscular strength of hamstrings and quadriceps and their possible muscular imbalance is considered by many authors as one of the causes of knee joint injury. The aim of this work is to assess the exercise program including squat modifications both in terms of progression of lower limb strength and in terms of possible change of H: Q ratio. Probands were divided into five groups (one control, four experimental). The experimental groups practiced the intervention program twice a week for eight weeks (EX1: Barbell squat, EX2: Barbell half squat, EX3: Barbell half squat with countermovement). In one training session participants repeated the exercise five times in six series. All experimental groups exhibited significant differences in mean values (p < 0.01), indicating the progression of lower limb strength measured by 1RM for barbell squat. The differences in the mean values of the H: Q ratio measured on an isokinetic dynamometer in the isokinetic test mode at angular velocities of 60 and 300 degrees per second do not show statistically significant differences (p = 0.99338). The established strength intervention program is suitable for the development of lower limb strength and does not show any changes in the H: Q ratio.